Attitudes and Actions of Unimed FIS Students in Ethics Viewed from a Pancasila Perspective - Adiputri, Cici; Simanjuntak, Duana Angel; Sunarti, Elisa (Holistic Science, 2024)
Ethics form the foundation of a student's character. A good student must also possess good ethics. However, not all students pay attention to ethics. Nowadays, there are many issues or cases of students lacking ethics in educational environments. The lack of respect for lecturers often becomes an ethical problem among students. For example, students not paying attention when the lecturer is speaking or explaining the material. Instances include students talking loudly with other students, playing with their phones, and being reprimanded by the teaching lecturer for disrupting the class and showing a lack of respect for the lecturer speaking. Thus, it can be concluded that there are still students who lack ethics in educational environments and they should know and apply ethics in such settings. The purpose of this research is to understand the knowledge and application of student ethics in educational environments. This study uses interview and observation methods. The population used in this research is students friom FIS UNIMED.